Fourier transform of hn(x + p)hn(x − p) - Mourad E. H. Ismail; Krzystztof Stempak (International Journal of Mathematics and Mathematical Sciences)
We evaluate Fourier transform of a function with Hermite polynomials involved. An elementary proof is based on a combinatorial formula for Hermite polynomials.